Rehabilitation of hand function after spinal cord injury using a novel handgrip device: a pilot study. - Hoffman, Haydn; Sierro, Tiffany; Tianyi Niu; Sarino, Melanie E.; Sarrafzadeh, Majid; McArthur, David; Edgerton, V. Reggie; Lu, Daniel C.; Niu, Tianyi (Journal of NeuroEngineering & Rehabilitation (JNER), 2017)
Background: Activity-based therapy (ABT) for patients with spinal cord injury (SCI), which consists of repetitive use of muscles above and below the spinal lesion, improves locomotion and arm strength. Less data has been published regarding its effects on hand function. We sought to evaluate the effects of a weekly hand-focused therapy program using a novel handgrip device on grip strength and hand function in a SCI cohort.Methods: Patients with SCI were enrolled in a weekly program that involved activities with the MediSens (Los Angeles, CA) handgrip. These included maximum voluntary contraction (MVC) and a tracking task that required each subject to adjust his/her grip strength according to a pattern displayed on a computer screen. For the latter, performance was measured as mean absolute accuracy (MAA). The Spinal Cord Independence Measure (SCIM) was used to measure each subject's independence prior to and after therapy.Results: Seventeen patients completed the program with average participation duration of 21.3 weeks. The cohort included patients with American Spinal Injury Association (ASIA) Impairment Scale (AIS) A (n = 12), AIS B (n = 1), AIS C (n = 2), and AIS D (n = 2) injuries. The average MVC for the cohort increased from 4.1 N to 21.2 N over 20 weeks, but did not reach statistical significance. The average MAA for the cohort increased from 9.01 to 21.7% at the end of the study (p = .02). The cohort's average SCIM at the end of the study was unchanged compared to baseline.Conclusions: A weekly handgrip-based ABT program is feasible and efficacious at increasing hand task performance in subjects with SCI.